## d/dx[cot(x)]

### To find the derivative of the function cot(x) with respect to x, we can use the quotient rule

To find the derivative of the function cot(x) with respect to x, we can use the quotient rule. The quotient rule states that for a function of the form f(x) = g(x) / h(x), the derivative is given by:

f'(x) = (g'(x) * h(x) – g(x) * h'(x)) / [h(x)]^2

In this case, g(x) = 1 and h(x) = tan(x). So, applying the quotient rule, we have:

cot'(x) = (1 * tan(x) – cot(x) * sec^2(x)) / [tan(x)]^2

To simplify further, we can use the trigonometric identities: tan(x) = sin(x) / cos(x), cot(x) = cos(x) / sin(x), and sec(x) = 1/ cos(x). Substituting these values, we get:

cot'(x) = [(sin(x) / cos(x)) * (1 / cos(x)) – (cos(x) / sin(x)) * (1 / cos(x))^2 ] / [(sin(x) / cos(x))^2]

cot'(x) = (sin(x) / cos^2(x)) – (cos(x) / sin(x)) / [(sin^2(x) / cos^2(x))]

cot'(x) = sin(x) / cos^2(x) – cos(x) / sin(x) * cos^2(x) / sin^2(x)

cot'(x) = sin(x) / cos^2(x) – cos(x) / (sin(x) * sin(x)) * cos^2(x)

cot'(x) = sin(x) / cos^2(x) – cos(x) * cos^2(x) / (sin(x) * sin^2(x))

Now, let’s simplify further by using the trigonometric identity: sin^2(x) + cos^2(x) = 1.

cot'(x) = sin(x) / cos^2(x) – cos(x) * cos^2(x) / (sin(x) * (1 – cos^2(x)))

cot'(x) = sin(x) / cos^2(x) – cos(x) * cos^2(x) / (sin(x) – sin(x) * cos^2(x))

cot'(x) = [sin(x) – cos(x) * cos^2(x)] / (cos^2(x) * (sin(x) – sin(x) * cos^2(x)))

Finally, we have obtained the derivative of cot(x) with respect to x, which is:

cot'(x) = [sin(x) – cos(x) * cos^2(x)] / (cos^2(x) * (sin(x) – sin(x) * cos^2(x)))

##### More Answers:

The Mathematics of Multiplying Rational and Irrational Numbers | Why the Result is Always IrrationalMastering Basic Arithmetic | Understanding the Sum and Product of Rational Numbers

Derivative of sec(x) | Using Chain Rule to Find the Derivative of the Secant Function